Seed production of ’Mombasa’ grass subjected to different closing cut dates and nitrogen rates - Canto, Marcos Weber do; Almeida, Gleice Menezes de; Costa, Antonio Carlos Saraiva da; Barth Neto, Armindo; Scaliante Júnior, João Ricardo; Orlandini, Carla Faria (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effects of closing cut dates (CCD) and nitrogen (N) rates on the components of pure seed yield (PSY) and seed quality in 'Mombasa' grass (Megathyrsus maximus 'Mombaça'), besides determining the parameters of apparent N efficiency (ANE) and agronomic N efficiency (AgNE). The field experiments were carried out over two growing seasons, 2010/2011 and 2011/2012, in Umuarama, PR, Brazil. The folllowing treatments were evaluated: CCD on October 10, January 31, February 15, and March 1; and N doses at 0, 75, 150, and 225 kg ha-1. Significant interactions between the CCD and N doses were observed for the panicle tiller number (PTN), pure seeds per panicle, PSY, ANE and AgNE. Values of ANE and AgNE were better for 150 kg N ha-1. There were no effects of CCD and N doses on seed quality. PSY was closely correlated with PTN, pure seeds per panicle, and pure seed number.The CCD treatments of longer growth duration and higher N doses showed the higher PSY. Final CCD delaying until February and N availability reduced yield. Closing cut date and N fertilization affect pure seed yield and yield component responses of 'Mombasa' grass.